Citrus hystrix L. condimentary leaves: proximate composition, fatty acids and sugars profile - Pereira, Carla (2018)
Citrus hystrix L., commonly known as kaffir lime, is a plant belonging to the citrus family (Rutaceae). It is native to South Ásia and Southeast Ásia, mostly occurring in Indonésia, Malaysia, the Philippines, Laos, Thailand, and Vietnam. Its leaves and fruit have been widely used for culinary and traditional medicine purposes. Contrarily to the fruit juice and pulp, which present a pungent taste and therefore are not directly consumed, the leaves are considered as the most important spice in these regions, being added to almost every dish, besides ginger and lemon grass [1,2]. Thus, given the wide application of kafiir lime leaves as condiment, the present study intended to assess its nutritional value, namely its proximate composition in carbohydrates, protein, ash, and fat, as well as its fatty acids and sugars profile by GC-FID and HPLCRI, respectively. Regarding the nutritional composition of the condimentary leaves, carbohydrates were the most abundant macronutrients (64. 7±0.2 g/100 g), followed by protein (17. 98±0.03 g/100 g), and ash (12. 96±0.06 g/100 g). In what concerns fatty acids, twenty-two compounds were detected, among which polyunsaturated fatty acids were prevalent (71. 5±0. 1%), with considerable percentages of linolenic (55. 6±0.2%) and linoleic (15.02±0.07%) acids. This spice alsopresentedpalmitic (15. 1±0.2%) and stearic (3. 6±0.2%) acids as the most abundant saturated fatty acids (26. 29±0. 05%); and oleic (1.243±0.003%) and palmitoleic (0.74±0.05%) acids as the main monounsaturated fatty acids (2. 05±0. 05%). In terms offree sugars, three molecules were identified, with sucrose (3. 5±0. 1 g/100 g) being detected in higher concentrations than fructose and glucose (0. 98±0.04 and 0. 72±0.03 g/100 g, respecüvely). Through the results obtained in the present study, it was possible to verify that kaíËr lime presents an equilibrated nutritional profile, which valorizes its use as condiment, beyond its só appreciated taste.